Preparation and Characterization of Gelatin-Based Films Cross-Linked by Two Essential Oils at Different Concentrations and Plasticized with Glycerol - El Kolli, H.; El Kolli, M. (Engineering, Technology & Applied Science Research, 2021)
Gelatin cross-linking has recently been discovered to be a very appealing method of producing gelatin-based films. The current research looks at various commercial gelatin (type B) films to improve their physical qualities. Bunium alpinum and bunium incrassatum essential oils (EOs) in two quantities (5% and 25%) were added to the films, which showed substantial biological activity (antibacterial, antioxidant, antihemolytic, and anti-inflammatory). According to electronic scanning microscopy, the basic gelatin matrix had changed and there were multiple dense spots on the cross-linked films. The particles appear to be more bonded in an isotropic form. Infrared spectroscopy cannot provide substantial accuracy on the new characteristics and chemical interactions formed due to the complex system of both gelatin and EOs. According to the UV transmission test results, adding EOs to gelatin films improves the barrier properties against UV rays and prevents UV light transmission. Finally, the swelling water test revealed that included EOs in the film composition reduce the film’s swelling.